Penguatan Aksesibilitas Permodalan bagi Peningkatan Daya Saing Pelaku Usaha Informal - Aryanto Nyuru Keiku; Harsono Harsono; Adi Suprayitno (University Merdeka Malang, 2022)
Creating a strategy that can encourage the competitiveness of informal business actors is still a difficult issue in Indonesia. Whereas competitiveness is the main key for informal business actors to continue to survive in the face of high intensity of business competition. On the other hand, many programs have been carried out, especially those related to strengthening the accessibility of capital for informal business actors. However, the program is relatively not optimal because the impact has not been significant. Based on these problems, the purpose of this study is to see how the impact of capital accessibility on income levels as a determinant of the competitiveness of informal business actors. Based on the in-depth interview and exploratory descriptive method, the results of the analysis show that informal business actors in Malang City who participate in the capital cooperation network have a higher income level, so that their competitiveness is relatively increased. A capital cooperation network was deliberately established to jointly access group network-based capital from informal business actors. Group networks are categorized as social capital, which determines the success rate of strengthening business competitiveness. These results can be used as a reference for the preparation of regulations to strengthen the competitiveness of informal business actors who are approached from strengthening the accessibility of capital.